Introduction to and Discussion Summary of Lin Yaofu's "Toward a Version of China: The Taiwan Experience" - Krieger, Murray (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
In the context of the Second International Conference on Humanistic Discourse, this text introduces Lin Yaofu's "Toward a Version of China: The Taiwan Experience" and reports on the central concerns that emerged in its discussion.